THE INFLUENCE OF SERVICE QUALITY, BRAND TRUST AND ADVERTISING ON PURCHASING DECISIONS FOR MAXIM TRANSPORTATION SERVICES IN BATAM CITY - Karangora, Agnesia Ina Peni; Saputra, Asron (LPPM Sekolah Tinggi Ilmu Ekonomi - Studi Ekonomi Modern, 2025)
The aim of this research is to analyze the influence of service quality, brand trust and advertising on purchasing decisions for Maxim transportation services in Batam City. This research uses descriptive research with quantitative methods and the sample used is 385 respondents who have purchased Maxim transportation services. research This was analyzed using SPSS version 25 software. The partial test results from this research show that the independent variables, namely service quality, brand trust and advertising, have a positive and significant influence on purchasing decisions for Maxim Transportation Services in Batam City.